R&D Expenses and Share Value in The Japanese Stock Market - Nivoix, Sophie; Ngunyen, Pascal (The Indonesian Capital Market Review, 2009)
The growing influence of technology in business activities is driving many firms to devote a greater amount of resources to research and development. It is therefore crucial to understand how the stock market evaluates the benefits of R&D. In this paper, our aim is to investigate whether Japanese investors have rewarded firms that heavily invest in R&D. We first document that R&D expenses have remained fairly stable relative to sales in the past eight years, but with large variations within and between industries. We then show that R&Dfirms have achieved a higher return relative to non-R&D firms. However, our regressions and investment simulations indicate that the relation between R&D intensity and stock returns is not significant, suggesting that the Japanese stock market is semi-strong efficient.